Connected we stand: A network perspective on trade and global food security. (November 2015) - Sartori, Martina; Schiavo, Stefano
Highlights: We ask whether globalization of food trade generates systemic instability. We apply network analysis to the global network of virtual water trade (1986–2010). The world has become more interconnected but not less stable. Global trade cannot be regarded as a major source of instability. International policy coordination crucial to make the world resilient to food crises. Abstract: We analyze the link between virtual water trade, that is, the flow of water embodied in the international trade of agricultural goods, and vulnerability to external shocks from the vantage point of network analysis. While a large body of work has shown that virtual water trade can enhance water saving on a global scale, being especially beneficial to arid countries, there are increasing concerns that openness makes countries more dependent on foreign food suppliers and, in this way, more prone to external shocks. Our evidence reveals that the increased globalization witnessed in the last three decades is not associated with the increased frequency of adverse shocks (in food production). Furthermore, building on recent advances in network analysis that connect the stability of a complex system to its topological features, we find that the world is more interconnected, but not necessarily less stable.